Oman novel literature since 1950 an analytical study with special reference to Celestial Bodies of Jokha Alharthi - Saji, T (MES Mampad College, University of Calicut, 2025)
The Omani novel has witnessed remarkable development in both quantity and quality in the twenty-first century, securing a significant place in the Arab literary scene. Among its most notable achievements is the Arabic Booker Prize: The Omani novel won the International Prize for Arabic Fiction in 2019 with Jokha Alharthi's novel Celestial Bodies, the first novel from the Gulf to win this award. The novel has also been translated into several international languages. Other Omani novels have made it to the longlists and shortlists of prestigious Arab awards, such as the Sheikh Zayed Award and the Katara Prize. Alongside Jokha Alharthi, names such as Huda Hamad, Zahran Al-Qasimi, Badriya Al- Shehhi, and Mohammed Al-Shuaili have emerged, offering powerful texts that are diverse in style and subject matter. The Omani novel has addressed several important issues, including identity, women, forgotten Omani history, social and political transformations, literary experimentation, modernity, and the relationship between the past and the present. Omani works have been translated into languages such as English, French, German, and Spanish, contributing to Omani literature reaching a global readership. Jokha Alharthi is a prominent Omani writer and academic, born in 1978. She is considered one of the most prominent figures in contemporary Omani and Arab literature. She earned a PhD in classical Arabic literature from the University of Edinburgh in the United Kingdom and works as a professor of literature at Sultan Qaboos University. She began writing at an early age and has published short story collections such as ‘Naranja’. Her most notable work is her novel ‘Sayyidathul Qamar’ (2010). It was translated into English as Celestial Bodies and won the Man Booker International Prize in 2019, making her the first Arab writer to win this award. Her other works include the novel "Naranja" (2016), the novel ‘Hareer Gazelle' (2021), and a collection of short stories and critical studies. Jokha Alharthi's literature is distinguished by its in-depth portrayal of Omani society, particularly from the perspective of women, and its treatment of themes such as tradition, identity, and social transformation.Celestial Bodies revolves around the lives of three Omani sisters—Mia, Asma, and Khawla—and through them conveys a multi-dimensional portrait of post- colonial Omani society, where social, political, and cultural transformations intersect with personal and family stories. The novel delves into women's issues, highlighting the internal conflicts experienced by female characters between tradition and modernity, and between individual ambition and social constraints. It also addresses the effects of past slavery and the impact of economic and cultural transformations on family and societal structures. Told in poetic language and a narrative intertwined between time periods, the author weaves a literary fabric that reflects the complexities and transformations of Omani identity, leading the novel to win the Man Booker International Prize in 2019 and becoming a landmark in contemporary Arab feminist literature. This research aims to discover the diverse literary features in the novel ‘Celestial Bodies’ which represent the elevation and development resulting from Omani novels in the modern era, by shedding light on the history of the development of the novel in the Sultanate of Oman and its characteristics. The research delved into various social issues faced by Omani society throughout the ages. The researcher analyzed some of the novel's structures and dimensions deconstructed the narrative techniques it contained, and expanded the worlds of the characters, their characteristics, and their interactions with certain events. The research analyzes linguistic elements from various perspectives. The researcher relied in this study on the descriptive analytical approach to complete this task through four chapters and twenty-three sections.